DIGITAL TRANSFORMATION IN HUMAN RESOURCE MANAGEMENT - Indarta Priyana; Isniar Budiarti; Silvy Sondari Gadzali (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Digital transformation has become an inevitable phenomenon in various aspects of business, including in human resource management. This article explores the importance of digital transformation in improving the effectiveness of human resource management and examines the challenges that may be faced during the implementation process. Digital transformation enables the automation of various routine activities such as employee data administration, wages, and benefits, which significantly reduces manual workload and the risk of human error. In addition, the application of technologies such as artificial intelligence and data analytics allows for a more efficient hiring process and more informed and rapid data-driven decision- making. However, this transformation process is not free from various obstacles, including resistance to change among employees, problems integrating existing digital systems, and data security threats. Resistance to change often arises due to fears of job loss or difficulty adapting to new technologies. Technical challenges also occur in terms of synchronizing the various systems used by the company and ensuring the security of employee data from cyber threats. Amidst all this, maintaining a balance between technological efficiency and human touch remains key. By facing and resolving these obstacles, companies can harness the benefits of digital transformation in human resource management, creating a more productive, adaptive and future-oriented work environment.